Oxidative stress and post-stroke depression - D. Komsiyska (Trakia Journal of Sciences)
The topic of post-stroke depression etiology is reviewed in two main approaches. Some suggest that post-stroke depression is caused by the brain damage itself. On the contrary, others assume that this is a psychologic response to injuries or loss. Many discoveries can be examined as evidence for both the physiological and psychosocial mechanism of post-stroke depression. The two methods are not self-excluding, but instead describe post-stroke depression as a complex and multifactorial disease with interactions between the physiological and environmental factor. One hypothesis about depression occurrence is the inflammatory, oxidative and nitrosative stress (IO&NS) depression theory. Oxidative stress mechanisms are implied in the pathogenesis of mental diseases. The brain is considered particularly vulnerable to oxidative damage, due to its relatively high oxygen utilization and thus generation of free radical subordinate products, its modest antioxidant protections and its lipid-rich resistance.